APLIKASI TEORI PERMAINAN DALAM PENENTUAN STRATEGI PEMASARAN PROGRAM STUDI TEKNIK INFORMATIKA DAN TEKNIK INDUSTRI - WIJAYATI, DIYAH; SUPRIYADI, EDI (E-Jurnal Matematika; Vol 10 No 2 (2021), 2021)
Competition in the world of education especially the highest level of education, is getting tougher in obtaining student. So that, needed to analyze the study program’s marketing strategies in facing this competition. The aim of this research is making decision to determine the optimal strategy of the study program using game theory which is solved by the linear programming method. The data in this study obtained from the Informatics and Industrial Engineering study program at Sekolah Tinggi Teknologi Bandung. From application game theory, it is recommended that game with mixed strategy is an appropriate one. Result show that the optimal marketing strategy for Informatics Engineering study program is number of graduation strategy, tuition fee strategy, and number of lecturer strategy. While the optimal marketing strategy for Industrial Engineering study program is tuition fee strategy, popularity strategy, and number of graduation strategy.